Mountain Selection for Beginner Climbers:a Simple Additive Weighting (SAW) Method - Liza Wikarsa; Michael George Sumampouw; Christofel Mario Tore (Journal of Information Technology and Its Utilization, 2024)
Over the years, mountain climbing has become more popular among ordinary people, with interest suddenly spiking during this recent time. A well-prepared and route-knowledgeable climber is most likely to win half the battle. The task of selecting a mountain for first-time climbers can be a daunting one. The Simple Additive Weighting (SAW) method can help beginner climbers determine which mountain is best for them. This method enables users to assign weights to each criterion and alternative based on their preferences, facilitating direct comparisons between options, and calculating all possible combinations, making the process faster and more accurate. According to this study, a campsite, mountain height, natural resources, mountain beauty, and terrain difficulty are major factors to consider when choosing a mountain. The alternatives consist of six mountains in North Sulawesi—Mount Klabat, Lokon, Soputan, Mahawu, Empung, and Tampusu—assessed according to the established criteria. In conclusion, the Decision Support System using the SAW method was successfully developed to help beginner climbers choose mountains based on their preferences. This system includes features such as mountain search, SAW calculations, and top recommendations. Future updates could consist of more detailed mountain specifications and a broader selection of mountains.